Empowering SMEs Through Product Innovation: A SWOT-Based Analysis of Income Enhancement in Maros Regency, Indonesia - Sharon, St Salmah; Muchtar, Muchtar; Basir, Mustika Kusuma (Technium Business and Management, 2025)
This study explores the role of product innovation in increasing the income of Micro, Small, and Medium Enterprises (MSMEs) in Maros Regency, Indonesia. Using a descriptive qualitative approach and case studies of local food-processing MSMEs, the research adopts an interpretive paradigm to understand business dynamics from the actors’ perspectives. SWOT analysis is employed to assess the strengths, weaknesses, opportunities, and threats of the innovation process. Findings reveal that product innovation—through product differentiation, attractive packaging, and the use of local materials—positively impacts income enhancement. Nonetheless, challenges such as limited capital, restricted market access, and insufficient digital skills persist. Opportunities arise from the growing healthy food trend and supportive local policies, while threats include intense competition and fluctuating raw material prices. The study contributes theoretically by enriching the discourse on innovation in semi-urban MSMEs, with originality rooted in its in-depth SWOT-based analysis of local entrepreneurial realities.